POTENTIAL APPLICATIONS KEPAYANG COMBINATION OF SEEDS AND CELERY POWER ON DURABLE QUALITY AND CHICKEN WITH VARIATION OF FUTURE SAVE - Yopi Hinggu Meha, Permata Ika Hidayati, Aju Tjatur Krisnaningsih (Jurnal Sains Peternakan, 2016)
ABSTRACT This study aimed to determine the effect of kepayang and celery seed characteristics microbiological, chemical, and physical with a variety of fresh chicken meat shelf life. The material used in this research, namely meat, kepayang, celery. The meat used in this study as much as 1 kg, obtained from Malang Klojen market. Method of research done on the experiment using completely randomized design (CRD), which consists of 4 treatments, Po: 0 hours, P1: 24 hours, P2: 36 hours, P3: 72 hours, with each treatment was repeated 3 times. The research variables including TPC, protein testing, organoleptic test. Analysis of data using a single anava, if there is a difference then continued with LSD and Duncan. The results showed that with the addition of chicken meat preservation kepayang seeds and celery with a variety of shelf life provides a significant influence (P